2011
DOI: 10.1016/j.jtbi.2011.04.016
|View full text |Cite
|
Sign up to set email alerts
|

A biomechanical model of swallowing for understanding the influence of saliva and food bolus viscosity on flavor release

Abstract: After swallowing a liquid or a semi-liquid food product, a thin film responsible for the dynamic profile of aroma release coats the pharyngeal mucosa. The objective of the present article was to understand and quantify physical mechanisms explaining pharyngeal mucosa coating. An elastohydrodynamic model of swallowing was developed for Newtonian liquids that focused on the most occluded region of the pharyngeal peristaltic wave. The model took lubrication by saliva film and mucosa deformability into account. Fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…This is probably because participants recognized this bolus as sol phase. Previous studies revealed that solution or sol type foods indicate less than 20 kPa in Young’s modulus [30]. Altogether, it was confirmed that the fabricated artificial food bolus reflects one's normal swallowing.…”
Section: Discussionsupporting
confidence: 59%
“…This is probably because participants recognized this bolus as sol phase. Previous studies revealed that solution or sol type foods indicate less than 20 kPa in Young’s modulus [30]. Altogether, it was confirmed that the fabricated artificial food bolus reflects one's normal swallowing.…”
Section: Discussionsupporting
confidence: 59%
“…Tactile and mouthfeel sensations occur after swallowing which reflect sensory properties of food coatings . This coating depends both on product characteristics and physiological parameters such as salivary flow, and could explain differences in aroma release curves . Until now no experimental study has been conducted on in vivo aroma release from real foods during the whole consumption process, from the beginning of mastication to the end of mouth cleaning, while considering the effect of saliva.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4]6 Such deformable substrates are particularly relevant from a biological perspective, and there have been a number of rigorous studies in recent years to fundamentally understand the mechanics of these scenarios. [7][8][9][10][11][12] The concerned interaction between the lubricating fluid and its confining boundaries may, in addition, be complicated by the transport of ionic species within the flow medium because of electro-chemical-hydrodynamic interactions. The resultant interactions between the compliant surface and electrostatic transport in the lubricating fluid are by no means straightforward and are yet to be addressed in a comprehensive manner by the research community.…”
Section: Introductionmentioning
confidence: 99%